Ethics and integrity in financial management: An exploratory study on Student Affairs Department of Universiti Utara Malaysia - Rose Fazlinda Yanti, Abd Rashid (2016)
Ethics and integrity has appeared to be one of the most important issues in managerial field across the globe. Due to the tremendous challenges in managerial field particularly in financial management, the need of high standard ethics and integrity is essential towards better organisation performance. Literatures have revealed the ethical violation in organisation in financial management is not only negatively affecting the organisation performance yet it could lead to bankruptcy. To ensure the implementation of high ethics and integrity of organisation particularly in organisation culture, as well as in leadership and ethics training, there is a need for evaluation of its implementation. This study aims to evaluate the implementation of ethics and integrity and how it contributes towards organisation performance. A real case study which is HEP UUM was used to fulfill the aims of this study. Mix method approach was applied for data collection which involved questionnaire and interview. The findings indicate that ethics in organisation culture, leadership and also training contributes much towards HEP UUM financial management performance. Results also illustrate that most of the employees believe that their organisation do have a proper ethical and ethics in term of organisation culture, leadership and ethics training in financial management. This finding could be used by the HEP UUM as guideline to fostering the implementation of ethics and integrity for a better performance.